Design and Implementation of Gamification-Based Arabic Language Learning Materials through the Quizizz Application to Enhance Students’ Motivation and Interactivity - Laiya, Fidya Fadila Safriana (Albariq: Jurnal Pendidikan Bahasa Arab, 2025)
This research aims to design and implement Arabic language learning materials incorporating gamification through the Quizizz application to enhance students’ motivation and interactivity. Grounded in the ADDIE model, this R&D study involved 60 students of MTs Al-Huda Gorontalo and one Arabic teacher, with expert validations from media, language, and content specialists. The needs analysis indicated that 89% of students perceived gamification as essential to overcoming boredom and passive engagement in Arabic learning. The developed media was validated as highly feasible by three experts: media (88%), content (89%), and language (92%). Implementation results showed a very positive response from students (83%) and the teacher (93%). The evaluation phase included a pretest-posttest analysis using SPSS 27. Descriptive statistics revealed a significant improvement: the average pretest score was 63.98 (CI 95%: 60.76–67.19), and the posttest score rose to 84.40 (CI 95%: 81.18–87.62). Normality tests indicated that the data did not fully meet the assumption of normality based on the Shapiro-Wilk test (pretest Sig. = 0.013; posttest Sig. = 0.001), although the Kolmogorov-Smirnov test for pretest was acceptable (Sig. = 0.200), allowing for parametric testing. The paired samples t-test confirmed a statistically significant difference (t = -12.677, df = 59, Sig. 0.000) with a mean difference between -23.639 and -17.194. These findings affirm that gamified learning materials significantly enhance student performance and engagement in Arabic instruction.